A Radical Feminist Reading of Stella Oyedepo’s Rebellion of the Bumpy-Chested in the Context of Yoruba Cultural Episteme - Sesan, Azeez Akinwumi; Iyanda, Rabiu (Journal of Gender and Power, 2024)
Feminist ideologies have permeated literary creativity and criticism across the globe. In this direction, literary writers have been adopting different styles in their feminist narratives reflecting and refracting conditions of women in patriarchal society. In the handling of feminist ideologies in literature, literary writers have been localising the tenets of feminism to reveal various experiences of women in male-dominate society. Stella Oyedepo, a Nigerian playwright and author of Rebellion of Bumpy Chested has engaged feminist ideology in critical discourse in her play. This paper adopts the tenets of radical feminism to content-analyse the play with a view to evaluating the consistence of the women’s action with the concepts of womanhood, wifehood and matrimony in Yoruba context. The actions of women, as shown in the plot of the play, are antithetical to the societal expectations of the gender specification of women. Their actions are culturally abnormal because Yoruba conception of womanhood has been violated in the agitations of women for better life and unbridled freedom. Radical feminism in Yoruba context is counter-productive because it breeds acrimony and disorderliness in society because Yoruba people believe in the ideology that men and women should complement one another for societal harmony.